2017
DOI: 10.21037/jtd.2017.02.30
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD47: the achievements and concerns of current studies on cancer immunotherapy

Abstract: Targeting CD47 is in the spotlight of cancer immunotherapy. Blocking CD47 triggers the recognition and elimination of cancer cells by the innate immunity. There are three CD47 antagonists in phase I clinical trials, but their potential efficacies are highly controversial. We raise our concern that NOD-based xenograft hosts tend to overestimate, while syngeneic mouse models could substantially underestimate the efficacy of anti-CD47 therapy. Such discrepancy may be resulted from specific reagent that alters CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 31 publications
0
90
0
Order By: Relevance
“…Recent studies have shown that CD47 blockade not only increases phagocytosis of cancer cells but also promotes cross presentation of tumor antigens by dendritic cells to enhance priming of antitumor effector T cells in syngeneic murine tumor models [25][26][27] . However, as demonstrated in both preclinical models 11 and human trials 28,29 , CD47 blockade using systemically delivered antibodies can result in anemia and thrombocytopenia due to high expression of CD47 on red blood cells and platelets respectively.…”
Section: Main Textmentioning
confidence: 99%
“…Recent studies have shown that CD47 blockade not only increases phagocytosis of cancer cells but also promotes cross presentation of tumor antigens by dendritic cells to enhance priming of antitumor effector T cells in syngeneic murine tumor models [25][26][27] . However, as demonstrated in both preclinical models 11 and human trials 28,29 , CD47 blockade using systemically delivered antibodies can result in anemia and thrombocytopenia due to high expression of CD47 on red blood cells and platelets respectively.…”
Section: Main Textmentioning
confidence: 99%
“…Anti-CD47 antibodies and small molecules that mimic the TSP binding site for bFGF are being tested in clinical trials, in preclinical models, or are under development for various diseases. 169,[178][179][180][181][182] Antagonists of these antiangiogenic TSP1 functions have not been tested with antagonists of TSP1's TGF-β activating function. Combined use of a variety of TSP1 functional antagonists could represent a multipronged approach to treating the complex pathogenesis of fibrosis.…”
Section: Tsp1 As a Therapeutic Targetmentioning
confidence: 99%
“…Hu5F9 is a humanized monoclonal antibody binding to CD47 with high a nity and has been proposed to activate a pro-phagocytic signal pathway to eliminate the tumor cells [13]. TTI-621 is a recombinant fusion protein composed of human SIRPα N-terminal domain fused to the Fc receptor of IgG, reinforcing phagocytosis and antitumor activity by engagement of macrophage Fcγ receptors with IgG1 Fc receptor [13,14]. However, the safety of these immune pharmaceuticals remains a key issue.…”
Section: Introductionmentioning
confidence: 99%